Night train to Lisbon [videorecording (DVD)] - Courtenay, Tom; Irons, Jeremy, 1948-; Lee, Christopher, 1922-2015; Rampling, Charlotte, 1946-; Olin, Lena; Mercier, Pascal, 1944- (Lionsgate, 2013)
Latin teacher Raimund Gregorius finds a book by Portuguese poet and doctor Amadeu de Prado and his life is irrevocably changed. Determined to learn more about the author, Gregorius boards the night train to Lisbon and begins to piece together an epic story of oppression and revolution, loyalty and betrayal, love and jealousy, played out against the backdrop of a brutal fascist dictatorship. In his exploration of Amadeu de Prado's life, Gregorius finds that life can change in an instant.